A Strengthened and Sensorised Custom Silicone Glove for use with an Intelligent Prosthetic Hand. (September 2022) - Kyberd, Peter J.; Findlayson, Duncan; Jayasuriya, Madhupani; Chibante, Felipe
Highlights: Silicone gloves for prosthetic hands can be made more durable with the addition of carbon nanofillers. Flexible touch sensors based Polypyrrole (PPy) and conductive cotton on can be made to be included in silicone prosthetic gloves. The sensors can be used in an hierarchical controller for a two degree of freedom multifunction hand. Abstract: External gloves for anthropomorphic prosthetic hands protect the mechanisms from damage and ingress of contaminants and can be used to create a pleasing, life-like appearance. The properties of the glove material are the result of a compromise between the resistance to damage and flexibility. Silicone gloves are easier to flex and keep clean, but also more easily damaged. This paper details the use of nanoclay fillers to enhance the properties of silicone, successfully increasing strength whilst maintaining flexibility. The performance of the enhanced silicone is as robust and resistant to tear and puncture as commercial gloves, while being more flexible. This flexibility makes the incorporation of a piezo-electric pressure sensor based on the EEonyx conductive fabric, practical. A sandwich of the cloth and copper fabric creates the sensor, which decreases in resistance with increasing pressure. The sensors are characterised and production variability within the silicone are tested. Three sensors are incorporated into a glove made to fit around a Southampton Intelligent Hand. The hand adapts its grip shape and force depending on the object held. The technology is adaptable and it can be incorporated in a glove produced to fit any prosthetic hand.